Two new alkaloids with carboxylic acid moieties from Portulaca oleracea and their anti-inflammatory effects. (December 2022) - Guo, Shengnan; Li, Huanfeng; Zhang, Mingbo; Lan, Xiujuan; Yang, Ying; Ying, Xixiang
Abstract: Two new alkaloids with carboxyl, identified as 8-(6, 7-dihydroxy-1, 2, 3, 4-tetrahydroisoquinolin-1-yl) octanoic acid and 5-(diethylamino)-2-(3-(diethylamino)-3-oxopropyl)-2-hydroxy-5-oxopentanoic acid named oleralkacid A and oleralkacid B, were isolated from Portulaca oleracea L. for the first time, whose structures were determined using spectroscopic methods including 1 D NMR, 2 D NMR, UHPLC-ESI-QTOF/MS and circular dichroism (CD). Subsequently, the anti-inflammatory effects of compounds on lipopolysaccharide-stimulated macrophages were studied, and the results showed that the compound 1 and 2 at 5 μM and 10 μM could significantly inhibit inflammatory mediator IL-1 β, respectively. Graphical Abstract: ga1 Highlights: Two new alkaloids with carboxyl were isolated from Portulaca oleracea L. The two alkaloids exhibited remarkable anti-inflammatory bioactivities. The finding provides a novel therapeutic potential for ulcerative colitis.